# Derivative Formulas

In the following, u and v are functions of x, and n, e, a, and k are constants. 1. f '( x) = lim
h →0

f ( x + h) − f ( x ) h

The Definition of the Derivative.

2.

d (k ) = 0 dx d ( k ( u ( x) ) ) = k du dx dx d n ( u ) = nu n−1 du dx dx d du dv (u + v ) = + dx dx dx d du dv (u − v ) = − dx dx dx
d ( uv ) = uv '+ vu ' dx

The derivative of a constant is zero.

3.

The derivative of a constant times a function.

4.

The Power Rule (Variable raised to a constant).

5.

The Sum Rule.

6.

The Difference Rule.

7.

The Product Rule.

8.

d ⎛ u ⎞ vu '− uv ' ⎜ ⎟= dx ⎝ v ⎠ v2 dy dy du = dx du dx d ( f ( g ( x) ) = f ' ( g ( x) ) g ' ( x ) dx d du ( sin u ) = cos u dx dx d du ( cos u ) = − sin u dx dx d du ( tan u ) = sec2u dx dx

The Quotient Rule.

9.

The Chain Rule.

10.

Another Form of the Chain Rule.

11.

The Derivative of the Sine.

12.

The Derivative of the Cosine.

13.

The Derivative of the Tangent.

14.

d du ( cot u ) = −csc2u dx dx d du ( sec u ) = sec u tan u dx dx d du ( csc u ) = − csc u cot u dx dx d (Sin −1u ) = 1 2 du dx 1 − u dx d ( Cos−1u ) = −1 2 du dx 1 − u dx d ( Tan −1u ) = 1 +1u 2 du dx dx d − ( Cot −1u ) = 1 + 1 2 du dx u dx
d (Sec−1u ) = 12 du dx u u − 1 dx d ( Csc−1u ) = −12 du dx u u − 1 dx d 1 du ( ln u ) = dx u dx d 1 du ( log a u ) = dx u ln a dx d u ( e ) = eu du dx dx d u ( a ) = au ln a du dx dx

The Derivative of the Cotangent.

15.

The Derivative of the Secant.

16.

The Derivative of the Cosecant.

17.

The Derivative of the Inverse Sine.

18.

The Derivative of the Inverse Cosine.

19.

The Derivative of the Inverse Tangent.

20.

The Derivative of the Inverse Cotangent.

21.

The Derivative of the Inverse Secant.

22.

The Derivative of the Inverse Cosecant.

23.

The Derivative of the Natural Log.

24.

The Derivative of the log to base a.

25.

The Derivative of e raised to a variable.

26.

The Derivative of a constant raised to a variable.